Edge Version Molecular Descriptors of Tetrameric 1, 3 Adamantane - Mohanappriya, G.; Vijiyalakshmi, D. (International Journal of Engineering and Technology, 2018)
Molecular descriptors (Topological indices) are the numerical invariants of a molecular graph which distinguish its topology. In this article, we compute edge version of topological indices such as Zagreb index, Atom bond connectivity index, Fourth atom bond connectivity index, Geometric Arithmetic index and Fifth Geometric Arithmetic index of tetrameric 1,3 adamantane.Â